The Institutionalization Paradox Of Political Parties: A Case Study Of Golkar (2020-2024) - Rahman Tahir; Jhon Simon; Tomi Jaffisa (Universitas Dharmawangsa Medan, 2026)
The issue of political party governance is intriguing to study in depth and holistically, especially from an academic perspective, specifically examining the governance of the Golkar party in North Sumatra when led by Musa Rajekshah, which is aligned with the transformation of the new Golkar paradigm, positioning Golkar as a modern political party that is program-oriented and problem-solving oriented. This study aims to analyse the institutionalization of the Party in North Sumatra for the period 2020-2024. This research employs a descriptive qualitative research design using a case study method. Understanding the chronological sequence of events, the data obtained were analysed based on the Political Party Institutionalization theory of Vicky Randall and Lars Svasand, as well as neo-institutional theory. Based on the findings and analysis, it shows that the Party for the period 2020-2024 has a well-described level of institutionalization, referring to the process by which a political party becomes stable, independent, and has strong roots both internally and externally in society, making it an institution that operates based on clear rules and ideology. Thus, the writer concludes that the victory of Golkar Party in North Sumatra during the 2024 Legislative Election was due to the implementation of good party institutionalization, strengthened by